Refining Supervisory Practices in the Field of Behavior Analysis: Introduction to the Special Section on Supervision - LeBlanc, Linda A. (Behav Anal Pract, 2016)
The rapid growth in the number of behavior analysts and aspiring behavior analysts creates an imperative for effective and efficient supervisory practices. Many behavior analysts receive little to no explicit instruction and mentoring in supervision practices while they are in training themselves. Those behavior analysts may then be expected to provide supervision for a range of individuals soon after graduation and certification and throughout the remainder of their career. The papers included in this special issue offer guidance for establishing and maintaining supervisory relationships, understanding the importance of each of the ethical guidelines for supervision, structuring group supervision experiences, managing problems that can arise during the course of a supervisory relationship, and arranging models of supervision within human service organizations.